Comparison of Accuracy in Cutting Dental Profiles Between Differential Methods Approach Upward with a Lower Approach to Making Straight Gear Wheels - Agustian, Ganda; A, Yufrizal; Irzal, Irzal (Teknomekanik, 2018)
In the world of industrial gear use, it cannot be denied, every machine in the industrial world uses a component, namely gears to move rotating power. For this reason, in making gears the precision of the gear profile must be considered. The purpose of this study is to compare the accuracy of cutting the dental profile between the approach differential method and the approach to the bottom. This research is an experimental research. Based on the results of data analysis on the comparison of the precision of cutting dental profiles between the approach differential methods and the approach to the bottom, the upward approach is more appropriate in terms of thickness and number of teeth. The number of samples used in the study of 12 gears consisting of 6 gears was carried out with the approach differential approach method, and 6 gears were carried out by the differential approach approach method. Each sample is measured in thickness and the number of teeth in a straight gear. After measurement, the data is processed using the t-test formula to see the significant difference in the accuracy of the dental profile. Based on the results of the t-test analysis that has been carried out there are differences in the gears produced. The approach to differential approach to getting better gear results.